Identifying and Supporting the Needs of People with Dementia and Their Families - Strengthening Communication Skills for Formal Carers - Morrisby, Claire (Curtin University, 2020)
This thesis investigated the needs of people with dementia and their carers from the perspectives of service providers and service recipients. Holistic needs and gaps in the understanding and support of people with dementia among existing dementia-care services were identified. An unmet need for better communication was addressed using an innovative communication training package - the Curtin University Empathy Simulator. This training proved beneficial for people living with dementia and those who care for them.